Learn CloudFormation Write, deploy, and maintain your AWS infrastructure - Kurniawan, Agus (Packt Publishing Limited, 2018)
bGet up and running with AWS automation using CloudFormation/b h4Key Features/h4 ulliExplore the fundamentals of AWS CloudFormation /li liGet acquainted with concepts such as CloudFormation templates and mappings /li liLearn to implement Infrastructure as a Code (IaC) on AWS /li /ul h4Book Description/h4 As the Amazon Web Services (AWS) infrastructure is gradually moving towards cloud, managing cloud-related tasks efficiently continues to be a challenge for system administrators. CloudFormation is a language developed for managing infrastructure-related services efficiently on AWS and its features help secure the AWS resource deployment process. Learn CloudFormation serves as a fundamental guide to kick-start your journey on CloudFormation. We will introduce you to the basic concepts on IaC and the AWS services required for implementing automation and infrastructure management. Then, we deep dive into concepts such as CloudFormation mapping, conditions, limit, and output and EC2. In the concluding chapters, you will manage the entire AWS infrastructure using CloudFormation templates. By the end of this book, you will get up and running with IaC with CloudFormation. h4What you will learn/h4 ulliUnderstand AWS CloudFormation /li liDevelop AWS CloudFormation templates /li liDeploy AWS CloudFormation for AWS resources /li liBuild your first AWS CloudFormation project /li liExplore AWS Security features /li liDeploy testing and production stages using CloudFormation/li/ul h4Who this book is for/h4 Learn CloudFormation is for cloud engineers, system administrators, cloud architects, or any stakeholders working in the field of cloud development or cloud administration. Basic knowledge of AWS is necessary